Long-Term Prognosis of Cognitive Function in Patients With Idiopathic Normal Pressure Hydrocephalus After Shunt Surgery - Kambara, Akihiro; Kajimoto, Yoshinaga; Yagi, Ryokichi; Ikeda, Naokado; Furuse, Motomasa; Nonoguchi, Naosuke; Kawabata, Shinji; Kuroiwa, Toshihiko; Kuroda, Kenji; Tsuji, Shohei; Saura, Ryuichi; Wanibuchi, Masahiko (Frontiers in Aging Neuroscience, 2021)
The long-term prognosis of cognitive function in patients with idiopathic normal pressure hydrocephalus (iNPH) remains unclear. This study aimed to determine the long-term prognosis of cognitive function in patients with iNPH, as well as the related factors. This study included 48 patients with iNPH who were treated with CSF shunting from January 2015 to December 2017 at Osaka Medical College Hospital and with follow-up evaluation of cognitive function for > 2 years. Cognitive function was measured using the Mini-Mental State Examination (MMSE) preoperatively and at 3 months, 1 year, and 2 years postoperatively. The preoperative MMSE score (22.4 ± 5.4) improved at 3 months (23.8± 5.0 [p = 0.0002]) and 1 year (23.7 ± 4.8 [p = 0.004]) postoperatively. However, at 2 postoperative years, the MMSE score returned to preoperative levels (22.6 ± 5.3). 　Univariate and receiver operating characteristic analyses were performed for the two groups to identify factors associated with cognitive prognosis. These groups included the cognitive decline group (11 [23%] patients; a decrease in the MMSE score by ≥ 2 points two years after surgery) and maintenance/improvement groups (37 [77%] patients). The long-term prognosis of cognitive was better for younger ages (p = 0.009) and patients with more mild symptoms (p = 0.035) in both groups. The cutoff for age and disease severity (idiopathic normal-pressure hydrocephalus grading scale; INPHGS) was 78 years (area under the curve [AUC] = 0.77) and 5 points (AUC=0.71), respectively. Seventy-seven percent of the cases showed improved maintained/improved cognitive function for 2 postoperative years. Age and disease severity (INPHGS score) were associated with cognitive prognosis, which suggests that early iNPH diagnosis and treatment may prevent long-term cognitive decline.